With God and Guitars: Popular Music, Socialism, and the Church in East Germany. Issue 3 (27th May 2017) - Rauhut, Michael
Abstract: In the socialist German Democratic Republic (GDR), the Church entered into a long-term, complex and productive symbiosis with popular music. Beginning in the 1950s, reform-minded pastors opened their doors to jazz, and, later, almost the entire spectrum of popular music could be found in their churches: from pop hits, beat, rock, blues to singer/songwriters and punk. The interplay between the Church and popular music gave rise to a highly unique communicative space, a counterpart to the rigidly organized public realm. Here, political dissidents took refuge from a repressive system and were free to examine their society critically. This political force infused the alliance of the Church and popular music in East Germany with an explosive quality. To examine the specifics of this alliance, this article traces three major trends: the assimilation of African-American music, the reform of the traditional religious hymn, and the linking of youth ministry with popular music. The analysis of these three trends illuminates the particularities of the relationship between the Church and popular music in the GDR from a quantitative, qualitative, and historical perspective.